Efficient parking control algorithms for self-driving cars. (23rd August 2019) - Tariq, Shahroz; Choi, Hyunsoo; Park, Heemin; Lee, Jae Won
We explored the problems which will soon arise while parking in car parks. These include structure of parking lot suitable for autonomous cars, finding the closest parking slot available, and navigation to the location. In this paper, we explored the problems which are soon to be faced while parking autonomous cars in parking lots. We provide two solutions for two different kind of parking method which are named as guided conventional parking and guided blocked parking. Both methods use a central server and the graph of the parking lot to guide the cars to the closest parking slots. With experiments, we have shown that our proposed methods should be effective for the guided parking for self-driving cars. We also created simulations to visually analyse the changes made in the parking lot at each step of the process. We compared both solutions and discussed their trade-offs in detail.